'Man is not truly one, but truly two': a positive reading of Robert Louis Stevenson's double - Garland, Kate E. (2018)
This thesis will explore the literary double – doppelgänger or other – in the works of Scottish author Robert Louis Stevenson (1850 – 1894). Through a consideration of the literary double found within three key texts, the short story ‘Markheim’, the novella a Strange Case of Dr Jekyll and Mr Hyde, and the novel The Master of Ballantrae: A Winter’s Tale, I shall undertake a reading which accounts for the influence Calvinism and Scottish Presbyterianism had upon Stevenson’s double. I shall demonstrate this by focusing on the relationship between the first and second self – the two selves which together constitute the double - evidencing my theory with Stevenson’s writings, in addition to those by John Calvin, and Scottish Presbyterian thought. Ultimately, I will suggest when viewed through a theological lens, Stevenson’s literary double can accommodate a positive reading of duality.